RETRACTED: Applications of the Land Degradation Index (LDI) in remote sensing-based land degradation studies: An analytical review - Hanadi Talib Ismail Al-Qaisi (Universitas Negeri Malang, 2026)
Retraction Notice Following a careful review of the publication history of the article entitled “Applications of the Land Degradation Index (LDI) in Remote Sensing-Based Land Degradation Studies: An Analytical Review,” published in Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, Volume 6, Issue 1 (2026), DOI: https://doi.org/10.17977/um063.v6.i1.2026.4, the Editorial Board has decided to retract the article. The decision was made after the journal received information that substantially similar material had previously been published in the Iraqi University Journal, Volume 76, Issue 1, on April 30, 2026. The author subsequently requested the retraction of the article from Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial. To prevent duplicate publication and to maintain the integrity of the scholarly record, the article has been retracted. The bibliographic record and this retraction notice will remain available for transparency. Readers are advised not to cite or rely upon the retracted article.